2018
DOI: 10.18632/oncotarget.25613
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of MCM2 correlates with the prognosis of ovarian clear cell carcinoma

Abstract: Highly malignant tumors overexpress the minichromosome maintenance 2 (MCM2) protein in the nucleus, which is associated with advanced tumor grade, advanced stage, and poor prognosis. In this study, we showed that MCM2 is highly expressed in clinical samples of ovarian clear cell carcinoma. Although MCM2 expression was mainly localized to the nuclei as in other cancers, a few cases exhibited cytoplasmic localization of MCM2. Surprisingly, tumor samples with cytoplasmic MCM2 demonstrated excellent prognosis, sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
(33 reference statements)
1
9
0
Order By: Relevance
“…Such a staining pattern may also be observed for the anti-MCM4 antibody. Our present data and other published data (Dumit et al, 2014;Aihemaiti et al, 2018) suggest that a subset of MCM2-7 proteins can be localized in the cytoplasm during interphase in higher eukaryotes, which leads to inhibition of DNA replication and cell proliferation. In higher eukaryotic cells, it is unclear whether MCM2-7 proteins shuttle between cytoplasm and nucleus during interphase, as they do in S. cerevisiae.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Such a staining pattern may also be observed for the anti-MCM4 antibody. Our present data and other published data (Dumit et al, 2014;Aihemaiti et al, 2018) suggest that a subset of MCM2-7 proteins can be localized in the cytoplasm during interphase in higher eukaryotes, which leads to inhibition of DNA replication and cell proliferation. In higher eukaryotic cells, it is unclear whether MCM2-7 proteins shuttle between cytoplasm and nucleus during interphase, as they do in S. cerevisiae.…”
Section: Discussionsupporting
confidence: 82%
“…Recently, it has been reported that cytoplasmic localization of MCM2 is significantly correlated with increased apoptosis in clear cell carcinoma, resulting in improved prognosis (Aihemaiti et al, 2018 -Kohno et al, 2008) MCM2-related fragment (Harada et al, 2008) 63 kDa 55 kDã 110~5 00 ATP-binding Zn-finger NLS NLS Fig. 6.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in our study, MCM2 played a protective role in CC progression; although consistent with previous studies [ 30 , 31 ], we also observed high expression levels of MCM2 in CC tissues. Aihemaiti et al reported that cytoplasmic rather than nuclear accumulation of MCM2 is related to improved survival for patients with ovarian clear cell carcinoma [ 32 ], which may be associated with MCM2-mediated DNA damage-induced apoptosis [ 33 , 34 ]. This pathway may also function in CC, although additional investigation is needed to explore this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced expression of licensing factors leads to more apoptosis in different cancers. In cell lines of gastric cancer, osteosarcoma, and cervical cancer, down-regulation of CDC6 promotes cell apoptosis, which negatively impacts growth in vivo and in vitro [40][41][42]. Moreover, partial overexpression of MCMs can enhance cell proliferation significantly and suppress apoptosis, whereas knockdown of MCMs reverses these effects [43][44][45].…”
Section: Replication Origin Licensing Factors and Cell Apoptosis And Survivalmentioning
confidence: 99%